UNVEILING DETERMINANTS OF CONSUMER ADOPTION INTENTIONS FOR BUY NOW, PAY LATER (BNPL) SERVICES IN GOODS PURCHASES - Sarah Sabir Ahmad; Azfahanee Zakaria; Nurdiyana Nazihah Zainal; Mhd Azmin Mat Seman (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The rising adoption of Buy Now, Pay Later (BNPL) services raises concerns about financial sustainability, as consumers increasingly rely on deferred payments. This study examines key determinants of BNPL adoption—financial flexibility, consumer behaviour, and perceived ease of use—through the lens of the Technology Acceptance Model (TAM) and the Theory of Planned Behaviour (TPB). A quantitative survey of 200 Malaysian BNPL users, analysed using multiple regression in SPSS, reveals that financial flexibility and consumer behaviour significantly drive BNPL adoption, while perceived ease of use has little impact. The findings suggest that consumers turn to BNPL primarily out of financial necessity rather than convenience, raising concerns about potential overspending and debt accumulation. This study highlights the urgent need for financial literacy programs to promote responsible BNPL usage and prevent financial distress. By providing empirical insights into BNPL adoption patterns, it informs policymakers and financial institutions on strategies to mitigate risks. Future research should explore broader demographic segments to enhance understanding of BNPL’s long-term implications.